Socio-Economic Status of Pomegranate Growers under National Horticulture Mission (NHM) in Solapur District and Constraints Faced by Them. (Indian Journal of Extension Education, 2013)
The present study was conducted to study socio-economic status of pomegranate growers in Sangola and Malshiras tehsils of Solapur district. It observed that nearly two third (60.83%) of pomegranate growers belonged to middle age between 33 to 56 years. More than two third (71.66 %) of pomegranate growers had used medium sources of information. Maximum number of pomegranate growers (77.50%) had medium level of scientific orientation. A majority of pomegranate growers (63.33 %) were in the medium level of planning orientation category. Nearly two third (65.83%) of the pomegranate growers belonged to medium risk orientation. The study pointed out that 47.50 per cent of the respondents possessed favourable attitude towards NHM. A majority of respondents (66.67%) had medium area under pomegranate cultivation (1 to 4 ha.). More than one-third (37.50%) of pomegranate growers had medium land holding between 4.01 to 10 ha. A majority of pomegranate growers (91.66 %) and (87.50%) had used radio and TV as source of information respectively. Very high majority (74.16%) of the pomegranate growers obtained information from friends/relatives, while nearly two third (62.50%) of pomegranate growers had always received information through Radio, followed by Newspaper (56.66 %) and Television (50.83 %). It was observed that under supply constraints, majority (100.00 %) of pomegranate growers had faced the constraint of lack of availability of disease resistant varieties.